2021
DOI: 10.3390/molecules26102939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thai Local Ingredient Odorants, Litsea cubeba and Garlic Essential Oils, on Brainwaves and Moods

Abstract: The functional food market is growing with a compound annual growth rate of 7.9%. Thai food recipes use several kinds of herbs. Lemongrass, garlic, and turmeric are ingredients used in Thai curry paste. Essential oils released in the preparation step create the flavor and fragrance of the famous tom yum and massaman dishes. While the biological activities of these ingredients have been investigated, including the antioxidant, anti-inflammatory, and antimicrobial activities, there is still a lack of understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…In addition, a significant rise in alpha and beta waves was found in all frequency bands, from SA to FA and LB to HB. Sattayakhom et al (2021) reported that the inhalation of LC had a sedative effect, which was observed from a decline in alpha and beta wave intensity; this was inconsistent with our results. Furthermore, the novel flavour of LC in combination with SM inhalation activated the alpha waves in all domains, thus increasing concentration and restfulness as well (Cho, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a significant rise in alpha and beta waves was found in all frequency bands, from SA to FA and LB to HB. Sattayakhom et al (2021) reported that the inhalation of LC had a sedative effect, which was observed from a decline in alpha and beta wave intensity; this was inconsistent with our results. Furthermore, the novel flavour of LC in combination with SM inhalation activated the alpha waves in all domains, thus increasing concentration and restfulness as well (Cho, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…The oil of L. cubeba reportedly contains up to 70% of citral and has thus garnered a lot of interest as a commercially vital crop source for the production of citral, which is otherwise widely extracted from Cymbopogon citrates (lemongrass) [85]. Citral is a monoterpene that has been used as an antispasmodic, analgesic, anti-inflammatory, antipyretic, diuretic and sedative in traditional medicine [85,86]. It was confirmed to reduce neuronal excitability via inhibitory neurotransmitter modification, which, in turn, aids anxiety, insomnia, convulsion, pain and cognitive deficits [86].…”
Section: % Ethanolic Leaf Extractmentioning
confidence: 99%
“…Citral is a monoterpene that has been used as an antispasmodic, analgesic, anti-inflammatory, antipyretic, diuretic and sedative in traditional medicine [85,86]. It was confirmed to reduce neuronal excitability via inhibitory neurotransmitter modification, which, in turn, aids anxiety, insomnia, convulsion, pain and cognitive deficits [86]. In addition to citral, aporphine alkaloids and lignans are also considered major active components identified in the fruits and roots of L. cubeba due to their anti-inflammatory, antithrombotic, analgesic and antinociceptive properties [87,88].…”
Section: % Ethanolic Leaf Extractmentioning
confidence: 99%
“…The L. cubeba essential oil also displayed its effect on anxiolytic and analgesic activities and prolonged sleeping in ICR mice [ 53 ]. Furthermore, the study on healthy female subjects demonstrated that L. cubeba essential oil has a sedative effect by decreasing alpha and beta wave powers [ 54 ]. In addition, L. cubeba essential oil can improve mood disorders and reduce confusion accompanied with decreased cortisol levels in the saliva of healthy subjects [ 55 ].…”
Section: P Athology Of Alzheimer’s Diseasementioning
confidence: 99%